Anostracan (Crustacea: Branchiopoda) zoogeography III. Australian bioregions - Rogers, D. Christopher; Timms, Brian V. (Zootaxa, 2014)
Anostracan bioregions were identified for Australia. These regions were quantitatively defined using species distributions compared through Jaccard’s Coefficient of Community Similarity, and qualitatively defined using regional soils data. Community assemblages are quantified using Fager’s Index of Recurring Species Groups. Substrate geochemistry was used to investigate additional relationships, but was limited by the constraints of available data. However, the highly salinized soils directly relate to Australia bearing the highest diversity of halophilic anostracan taxa. Three anostracan biogeographical regions are defined for Australia: Western, Eastern and Southern.